TERAPI KOMPREHENSIF DAN PELAYANAN KESEHATAN TRADISIONAL BERBASIS BSM PENDEKATAN TCM PADA KASUS ANEMIA DI RUMAH PIJAT DHI - JAKARTA - Soesantono Delima; Hilman Rama Pratama; RM. Alfian; Ratna Dewi Putri (Journal of Innovation Research and Knowledge, 2025)
Anemia is a global health problem with high prevalence, particularly in developing countries such as Indonesia. Conventional therapies like iron supplementation and blood transfusion often have limited effectiveness and potential side effects, highlighting the need for alternative approaches. This study aimed to evaluate the effectiveness of a comprehensive therapy combining Traditional Chinese Medicine (TCM) and Body Space Medicine (BSM) for anemia patients at Rumah Pijat DHI – Jakarta. Aqualitative case study was conducted on three patients between July 20–25, 2025. Interventions included BSM acupressure, GITA exercise (Dong Yi Gong), abdominal massage, back tapping, and energy point stimulation. Data were collected through observation, interviews, tongue documentation, and vital sign evaluation. Results showed significant improvements in clinical symptoms, energy, sleep quality, and tongue appearance (from pale to normal), with no adverse effects observed. Comprehensive TCM-BSM therapy proved safe and potentially effective as an alternative treatment for anemia